If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 60 = 5t + -17t Combine like terms: 5t + -17t = -12t 60 = -12t Solving 60 = -12t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '12t' to each side of the equation. 60 + 12t = -12t + 12t Combine like terms: -12t + 12t = 0 60 + 12t = 0 Add '-60' to each side of the equation. 60 + -60 + 12t = 0 + -60 Combine like terms: 60 + -60 = 0 0 + 12t = 0 + -60 12t = 0 + -60 Combine like terms: 0 + -60 = -60 12t = -60 Divide each side by '12'. t = -5 Simplifying t = -5
| 46-7x=2x+18 | | 7=2-y | | 9x+6=4x+41 | | 7=2-8-x | | 25-2n=3n | | 5-8x=39-22x | | 121-5x=3x+17 | | -12.016+2.7p=-4.4(p-5.3)-5.52p | | 10n-8=3n-1 | | 5x+10=-102-9x | | y=4.72+3 | | 151-4x=6x+11 | | x^2+2x+4=4 | | 24a+6a-3(10)=6 | | -2-5x=14-9x | | 85-6x=7x+20 | | 2x+13=41-2x | | 5x+8=3x+26 | | 2x+6x=38 | | 11x-143=2x-8 | | 9x-26=82 | | -3n=10 | | 21x^2-8x=0 | | 4x-4=2x+10 | | -2(5+6c)+6=-90 | | 7.0544+2.17x=-4.8(2x+5.2) | | 4x+29=14x-91 | | 4x+29=14x-19 | | 3(x+1.26)=2x | | 8x+6-9x=28 | | 4x^3-12x^2+15x-7=0 | | 40(a-16)=80 |